Efektivitas Mindfulness Based Intervention: Doa Memohon Kesembuhan Terhadap Penurunan Kecemasan Pasien Pre-Operasi Di RS Permata Hati - Alvionita, Prafika; Ramadia, Arya; Rahmaniza; Fadhli, Rohmi (Jurnal Keperawatan Muhammadiyah, 2025)
Preoperative anxiety is a psychological response that occurs in patients who are about to undergo surgery. Anxiety that is not managed properly can affect the patient's physiological stability, such as increased blood pressure and heart rate, which can interfere with the course of the operation or even potentially cancel the operation. One approach that can be used to reduce anxiety is Mindfulness-Based Intervention (MBI) in the form of prayer for healing. Mindfulness techniques that encourage individuals to be fully aware of being fully present coupled with prayers that provide a sense of calm can play a role in anxiety management. The purpose of this study was to determine the effectiveness of mindfulness-based intervention praying for healing on reducing the anxiety of pre-operative patients at Permata Hati Hospital. This study used a Quasy experimental design using a pretest-posttest design with two group designs. The sample of this study was 32 people divided into two groups, the sampling technique used consective sampling. Data analysis was carried out using the Wilcoxon signed Rank Test. The results of the study, based on statistical tests, there is an effectiveness of mindfulness based intervention praying for healing on reducing anxiety of pre-operative patients with a p value = 0.000 (<0.05). In the intervention group more than half (56.3%) of respondents in the category of moderate anxiety level, the average pretest anxiety score was 28.63 and postest was 14.63. while in the control group most (68.8%) respondents in the category of severe anxiety level, the average pretest anxiety score was 29.06 and postest was 29.19. Mindfulness-based intervention in the form of praying for healing is effective in reducing the anxiety of pre-operative patients. Therefore, this intervention can be considered as an additional method in preparing patients before surgery.